Toleransi Antar Umat Beragama Dalam Perspektif Al-Quran - Ali Akbar; Edi Hermanto; Guslina Siregar; Naila Agnia Ramadhani; Saima Putri Nurfatimah Nst (Jurnal Ilmu Sosial dan Humaniora, 2025)
In today’s world, characterized by an ever-growing mix of different cultural, religious, and ideological perspectives, it is unavoidable for individuals to engage with one another. This rich diversity serves as a positive force that enhances community bonds and fortifies social cohesion. Nevertheless, religious variances often lead to misunderstandings, strains, and, at times, disputes that threaten fundamental human values. Consequently, it is crucial to reflect on the principles of tolerance highlighted in Islamic teachings, especially those found in the Qur’an. As the sacred text for Muslims, the Qur’an embodies key tenets of tolerance, illustrated in Surah Al-Kafirun verse 6: “To you your religion, and to me mine," alongside Surah Al-Baqarah verse 256: “There is no compulsion in religion.” These passages convey that Islam values religious freedom and recognizes differing beliefs. This spirit of tolerance is not merely theoretical; it was actively demonstrated by the Prophet Muhammad (peace be upon him). Throughout his life, the Prophet coexisted with adherents of other faiths, including Jews and Christians, and fostered harmony through the Charter of Medina, securing the rights and responsibilities of all Medina's inhabitants, irrespective of their faith. In Islam, tolerance does not entail the dilution or merging of beliefs but guides Muslims to uphold their convictions while honoring the faiths of others, fostering a peaceful, just, and harmonious society that is prosperous and civilized.